2020
DOI: 10.1097/bot.0000000000001749
|View full text |Cite
|
Sign up to set email alerts
|

Supplemental Fixation of Supracondylar Distal Femur Fractures: A Biomechanical Comparison of Dual-Plate and Plate-Nail Constructs

Abstract: Objectives: This biomechanical study compares the effectiveness of dual-plate (DP) and plate-nail (PN) constructs for fixation of supracondylar distal femur fractures in synthetic and cadaveric specimens. Methods: Twenty-four synthetic osteoporotic femurs were used to compare 4 constructs in an extra-articular, supracondylar fracture gap model (OTA/AO type 33-A3). Constructs included: (1) distal lateral femoral locking plate (DLFLP), (2) retrograde intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
58
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 24 publications
0
58
0
Order By: Relevance
“…In type C fractures, the distance from the lower border of the fracture line hot zone to the joint line was approximately 5 cm, and the perpendicular length of the hot zone was about 4 cm. Although the distance of the hot zone measured on the femur template can only be used as a reference, osteotomy gaps created in the former studies (18)(19)(20)(21)(22) were not long enough to accurately simulate the fracture morphology, which may underpower the results drawn from those studies. According to the scale of the template model, we suggest that for type A fracture model, the osteotomy gap should be made approximately 4 cm and the supracondylar osteotomy at 4 cm proximal to the joint line.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In type C fractures, the distance from the lower border of the fracture line hot zone to the joint line was approximately 5 cm, and the perpendicular length of the hot zone was about 4 cm. Although the distance of the hot zone measured on the femur template can only be used as a reference, osteotomy gaps created in the former studies (18)(19)(20)(21)(22) were not long enough to accurately simulate the fracture morphology, which may underpower the results drawn from those studies. According to the scale of the template model, we suggest that for type A fracture model, the osteotomy gap should be made approximately 4 cm and the supracondylar osteotomy at 4 cm proximal to the joint line.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a modified surgical incision to the distal femur such as the ''Swashbuckler'' approach described by Starr et al (25) should be considered by orthopaedic surgeons in preoperative planning. Meanwhile, although the biomechanical study has found that double plate constructs provided more stable fixation than lateral plate + retrograde intramedullary nail (rIMN) constructs (19), lateral plate + rIMN constructs may be more suitable in type A3 fracture cases with dispersed medial comminuted metaphysis due to a lack of medial exposure.…”
Section: Discussionmentioning
confidence: 99%
“…[6,[23][24][25][26][27] Two recent biomechanical studies have looked at PN fixation of distal femur fractures. [4,5] Neither study evaluated the effect of nail diameter on construct stiffness. In the clinical setting, the effect of nail diameter has been evaluated in geriatric proximal intertrochanteric femur fractures.…”
Section: Discussionmentioning
confidence: 99%
“…Specimen mounting and testing followed a previously published protocol. [5] Briefly, specimens were first loaded in torsion using a custom testing jig on an Instron testing machine (Instron Model 3365, Norwood, Massachusetts). Torque was applied along the femoral mechanical axis in internal rotation to mimic internal rotation of the tibia during normal knee flexion.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation